Oxidative stability and shelf life of avocado oil extracted cold and hot using discard avocado (Persea americana) - Guillén-Sánchez, Jhoseline (2020)
During the last years, the world avocado trade is on the rise, however, approximately 20% of the production is rejected for low caliber. This avocado discarded by low caliber can be used in the elaboration of other products, to give it added value. The objective of this study was to determine the shelf life of Hass avocado oil, type of discard, obtained by: (a) Drying by stove/Soxhlet (b) Lyophilized/Expeller. For the physicochemical characterization of the oil, density, melting point, acidity index, refractive index, iodine index and peroxide index were determined. The induction time was carried out by the RANCIMAT method, for which three temperatures of 140 °C, 160 °C and 180 °C were used and the shelf life of the oil was obtained by extrapolation at 25 °C. The results indicate that there is a significant statistical difference in the physicochemical characteristics of both oils. The shelf life was for the oil obtained by drying stove/Soxhlet 5.94 years and for the oil obtained by freeze-dried/Expeller 4.41 years, since both oils had a high content of unsaturated fatty acids 16.98% and 17.12%, respectively. In conclusion, it is possible to reduce post-harvest losses by obtaining avocado oil with high nutritional and functional qualities.